Implementasi Pemeliharaan Ikan Patin di Kolam Berbasis Pakan Herbal Kunyit Putih untuk Meningkatkan Produktivitas dan Ketahanan Pangan Kelompok Budidaya Pokdakan Bangun Makmur di Desa Parit Aman, Kecamatan Bangko, Kabupaten Rokan Hilir - Rusliadi Rusliadi; Heri Masjudi; Usman M. Tang; Mira Rahmita Sari; Hendrini Renolafitri; Morian Saspriatnadi; Zuqni Meldha; Lisa Legawati; Rahma Aprianti; Anelia Diah Wintang Sari (Unri Conference Series: Community Engagement, 2025)
Bangun Makmur Fish Farming Group in Parit Aman Village, Bangko District, Rokan Hilir Regency, participated in a community service program focusing on catfish farming technology through the integration of white turmeric-based herbal feed and rabal probiotics. This initiative aimed to enhance productivity, reduce production costs, and strengthen food security and the local economy. The program was implemented through training, field practice, mentoring, and continuous evaluation using a learning by doing approach. The results indicated notable improvements in farming performance. The use of white turmeric herbal feed reduced the Feed Conversion Ratio (FCR) to as low as 1.5, decreased feed costs by 28%, and increased fish harvest weight by 15 25%. The application of rabal probiotics contributed to more stable water quality, lowered fish mortality to below 15%, and improved water-use efficiency. In addition to technical outcomes, group members improved their management capacity by adopting Good Aquaculture Practices (CBIB), digital record-keeping, and online marketing strategies. Overall, the program demonstrated that combining herbal feed and probiotic technology with strengthened management practices is an effective strategy to promote economic independence and establish aquaculture as a sustainable alternative to secure food and livelihoods in rural communities.